Electrophysiological examination in uveitis: a review of the literature - Moschos MM (Dove Medical Press, 2014)
Marilita M Moschos,1 Nikolaos S Gouliopoulos,1 Christos Kalogeropoulos2 1Laboratory of Electrophysiology, First Department of Ophthalmology, University of Athens, Athens, Greece; 2Department of Ophthalmology, University of Ioannina, Ioannina, Greece Purpose: Uveitis is the inflammation of the uveal tract, which usually also affects the retina and vitreous humor. The electrophysiological examination is an objective ocular examination that includes the electroretinogram, visual evoked potentials, the electrooculogram, the multifocal electroretinogram, and multifocal visual evoked potentials. Our aim is to review the literature of the use of the electrophysiological examination in cases of uveitis. Methods: We performed a systematic search of the literature of published papers until October 2012 using the PubMed search engine. The key terms that were used were “uveitis,” “electrophysiological examination”, “electroretinogram”, “visual evoked potentials”, “electro-oculogram”, “multifocal electroretinogram”, and “multifocal visual evoked potentials” in multiple combinations. To the best of our knowledge, this is the first review concerning the assessment of electrophysiology in uveitis. Results: Our search of the literature demonstrated that the electrophysiological examination, mainly by means of electroretinogram, multifocal electroretinogram, and visual evoked potentials, is performed in several cases of uveitis for many purposes, including diagnosis and monitoring of disease progression and treatment efficacy. The electrophysiological examination is more useful in patients with multiple evanescent white dot syndrome, acute posterior multifocal placoid pigment epitheliopathy, birdshot chorioretinopathy, Vogt–Koyanagi–Harada disease, Adamantiades–Behçet disease, ocular syphilis, and Fuchs heterochromic cyclitis. Conclusion: This review summarizes the use of the electrophysiological examination in uveitic patients and underlines its value as a useful tool in the objective assessment and the monitoring of the disease. Keywords: uveitis, ERG, mfERG, VEP